2013
DOI: 10.1186/1743-0003-10-24
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of event-related desynchronization in robot-assisted hand performance: brain oscillatory changes in active, passive and imagined movements

Abstract: BackgroundRobot-assisted therapy in patients with neurological disease is an attempt to improve function in a moderate to severe hemiparetic arm. A better understanding of cortical modifications after robot-assisted training could aid in refining rehabilitation therapy protocols for stroke patients. Modifications of cortical activity in healthy subjects were evaluated during voluntary active movement, passive robot-assisted motor movement, and motor imagery tasks performed under unimanual and bimanual protocol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
95
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 49 publications
10
95
0
1
Order By: Relevance
“…This has been shown for self-paced voluntary movement (Crone et al, 1998b) passive movement (Alegre et al 2006; Formaggio et al, 2013), and imagined movement (Formaggio et al, 2013). Alpha-beta ERD is typically represented broadly across the sensorimotor cortex (Pfurtscheller et al, 2003), occurs prior to movement initiation, and is thought to represent a “pro-kinetic” state of increased cortical responsiveness (Crone et al, 1998b).…”
Section: Discussionmentioning
confidence: 70%
“…This has been shown for self-paced voluntary movement (Crone et al, 1998b) passive movement (Alegre et al 2006; Formaggio et al, 2013), and imagined movement (Formaggio et al, 2013). Alpha-beta ERD is typically represented broadly across the sensorimotor cortex (Pfurtscheller et al, 2003), occurs prior to movement initiation, and is thought to represent a “pro-kinetic” state of increased cortical responsiveness (Crone et al, 1998b).…”
Section: Discussionmentioning
confidence: 70%
“…Online adjustment of the timing and speed of instructive visual stimulation could further improve BCI training on the ERD production. Third, the current study focused only on visual information, while somatic sensation is also known to evoke ERD even when limbs are moved passively by a human experimenter (Alegre et al, 2002), a robot (Formaggio et al, 2013), or by functional electrical stimulation (Müller et al, 2003). Therefore, combining visual and somatosensory stimulation for MI-based BCI training may be worth to investigate if multisensory integration is more effective, although concurrent presentation of multimodal sensory stimuli sometimes disturbs ERD production (Takata et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…One reason is that, when wearing the exoskeleton, the right arm will move following the exoskeleton, which causes some problems in practical use because the movement of the right arm would produce ERD/ERS patterns over the hand area and this can result in false decisions of the system [27], especially an effect on the classification of left hand movement. Even if the right arm movement is a passive movement, it can also result in the ERD/ERS patterns similar to those in voluntary movements [40]. A related work [41] about passive movement effect found that the ERD/ERS patterns associated with upper limb movements are not significantly changed by periodic lower limb passive movements, which is similar to our results (the right hand movement mainly affects the classification of left hand movement, but not foot movement, as shown in Figure 7).…”
Section: Discussionmentioning
confidence: 99%